Organizational Culture Factors Affect Employees’ Organizational Commitment: A Research in Ho Chi Minh City Logistics Enterprises, Vietnam - Hien Dang The; Phu Tran Quang; Lien Bui Thi Bich; Nguyen Tran Thai Ha (Jurnal Manajemen Bisnis, 2022)
Research aims: The research aims to evaluate several factors of organizational culture affecting the organizational commitment of employees in logistics enterprises in Ho Chi Minh City (Vietnam).Design/Methodology/Approach: The data were collected based on a survey of respondents who were employees working at logistics enterprises in Ho Chi Minh City. The collected data, consisting of 227 survey questionnaires, were described through statistical analysis, checking Cronbach’s Alpha reliability assessment, employing Exploratory Factor Analysis (EFA), and testing the fit of the research model. Research findings: The results showcased that five components had a statistically significant impact on an employee’s organizational commitment, including (from high to low impact in order) consistency in governance policy, communication within the organization, training and development, rewards and recognition, and teamwork.Theoretical contribution/Originality: The study contributes to and supplements the array of organizational culture topics related to the commitment of employees at companies.Practitioner/Policy implication: The research contributes to the logistics companies' understanding of how to improve the organizational culture to maintain the loyalty of employees in the organization.Research limitation/Implication: The research limitation is that only Ho Chi Minh City logistics enterprises were chosen for the survey. However, there are many cities in Vietnam where logistics companies are located. Thus, the other research can be implemented in other regions in Vietnam and other countries for future studies.